Specification for wire for solid, cold-forged rivets of aluminium-copper-magnesium-silicon-manganese alloy (not exceeding 10 mm diameter) (Cu 4.4, Mg 0.5, Si 0.7, Mn 0.8). (31st August 1971) - British Standards Institution,
No abstract available